EXEHDA-DEP - An Architecture to Distributed Complex Event Processing - Souza, Weslen; Pernas, Ana Marilza (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2020)
In this work, EXEHDA-DEP is presented, a distributed architecture focused on the processing of complex events in the IoT, able to deal with the heterogeneity arising from these means and execute in environments that have or not connection restrictions. The results obtained demonstrate the capacity of EXEHDA-DEP to scale horizontal processing linearly, applying strategies that favor the design of an architecture with stable network consumption, where the tests performed demonstrate the stability of network consumption even with the continuous increase processing nodes.